2020
DOI: 10.1039/d0ma00023j
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nano-fiber forest foundation for ruthenium oxide pseudo-electrochemical capacitors

Abstract: Effect of ruthenium oxide coating temperature on directly grown carbon nanofibers for supercapacitor application is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…However, the capacitances of EGO and EGO-ABA-5 at 5 mV s −1 are lower than those at 10 and 20 mV s −1 , which is unusual, indicating that the electrodes’ surface area is less accessible at the lowest scan rate. Other studies have reported similar trends with carbon materials and it was proposed that the structure of the materials collapses when scanning at low scan rate or charging at low current density [ 63 , 64 ]. Furthermore, the specific capacitances of EGO-ABA-5 and EGO-ABA-10 are much larger than that of EGO-ABA-40 and of EGO.…”
Section: Resultsmentioning
confidence: 66%
“…However, the capacitances of EGO and EGO-ABA-5 at 5 mV s −1 are lower than those at 10 and 20 mV s −1 , which is unusual, indicating that the electrodes’ surface area is less accessible at the lowest scan rate. Other studies have reported similar trends with carbon materials and it was proposed that the structure of the materials collapses when scanning at low scan rate or charging at low current density [ 63 , 64 ]. Furthermore, the specific capacitances of EGO-ABA-5 and EGO-ABA-10 are much larger than that of EGO-ABA-40 and of EGO.…”
Section: Resultsmentioning
confidence: 66%
“…Several review papers on various PVSC, 12‐29 EES devices, 29‐48 and integrated systems 1‐12 have been published recently. As much as 90% of the worldwide PV market is currently dominated by the first‐generation Si‐based PVSCs, which have a high power conversion efficiency (PCE) as high as 27%, 12,21 as well as good stability and fixed industrial production standards.…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuels, which are limited natural resources, are being highly exploited due to the urgent need to meet the higher energy demands of society as well as the fast pace of technical advancements in the twenty-first century [ 1 , 2 , 3 , 4 ]. The rapid depletion of fossil fuels and the associated environmental pollution must be addressed with the research and development of green and renewable energy technologies for the continuous supply of secure and reliable energy [ 5 , 6 , 7 ]. Industrial and academic research is currently focusing on the alternative harnessing of energy in an efficient manner to fulfill these energy demands [ 8 ].…”
Section: Introductionmentioning
confidence: 99%